2020
DOI: 10.4236/ajps.2020.118082
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes Associated with Nickel Resistance in White Spruce (<i>Picea glauca</i>) under Nickel Stress: Analysis of AT2G16800 and <i>NRAMP</i> Genes

Abstract: Heavy metals such nickel (Ni) can cause toxicity by 1) displacing essential components in the biomolecules, 2) blocking the functional group of molecules, or 3) modifying enzymes, proteins, the plasma membrane, and membrane transporters. The main objective of the present study was to investigate the effect of nickel (Ni) on gene expression of nitrate on gene expression with a focus on the genes coding for the high affinity Ni transporter family protein AT2G16800, and natural resistance-associated macrophage pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Effects of nickel ions on gene expression in conifer species has been recently studied. Boyd and Nkongolo [ 56 ] reported a significant increase of AT2G16800 , and NRAMP expression in Picea glauca root samples treated with different concentrations of Ni compared to water. They also revealed that Ni induces an upregulation of ACCD at low and high doses tested in roots.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of nickel ions on gene expression in conifer species has been recently studied. Boyd and Nkongolo [ 56 ] reported a significant increase of AT2G16800 , and NRAMP expression in Picea glauca root samples treated with different concentrations of Ni compared to water. They also revealed that Ni induces an upregulation of ACCD at low and high doses tested in roots.…”
Section: Discussionmentioning
confidence: 99%
“…In Pinus banksiana and Pinus strobus, excess nickel prompted downregulation of the gene encoding the natural resistance-associated macrophage protein (NRAMP3) [22]. In contrast, this gene was upregulated in Picea glauca under conditions of excess nickel [23]. In some species, NRAMP3 is localized to the vacuole membrane, implying a possible role in nickel sequestration into the vacuole [24,25].…”
Section: Introductionmentioning
confidence: 99%